Reorganization of the connectivity between elementary functions as a common mechanism of phenomenal consciousness and working memory: from functions to strategies - Mogensen, Jesper (Philos Trans R Soc Lond B Biol Sci, 2018)
In the present communication, phenomenal consciousness, access consciousness and the closely related concept of working memory are presented in the context of a neurocognitive model—the REF (reorganization of elementary functions) framework. The REF framework is based on connectionist networks within which the ‘units’ are advanced processing modules called elementary functions (EFs). In this framework, the focus is on dynamically changeable ‘strategies’—based on reorganizations of the connectivity between EFs—rather than on the more traditional ‘cognitive functions’. The background for the REF framework and especially how the neural correlate of consciousness is understood within these models is summarized. According to the REF framework, phenomenal consciousness cannot ‘overflow’ availability of information for action. Phenomenal consciousness may, however, overflow working memory because working memory in the present context is seen as a surface phenomenon reflecting underlying dynamic strategies—influenced by both experience and situational factors. This article is part of the theme issue ‘Perceptual consciousness and cognitive access'.